Peran Penyuluh Antikorupsi Dalam Mengembangkan Komunitas Puskesmas Antikorupsi (Kompak) Studi Kasus: Puskesmas Di Kabupaten Bogor Jawa Barat - sudiman, dina indriyanti (Jurnal Inspirasi, 2019)
Abstract Previous research discusses cases of corruption and efforts to eradicate corruption in a repressive manner and the massive impact of corruption due to the increasing number of criminal acts of corruption occurring in public service units in Indonesia. However, in this study, the author focuses on the role of anti-corruption counselors as part of efforts to prevent corruption in the form of education on corruption eradication in Indonesia. Educative efforts carried out as a form of support to the KPK from attacks to weaken the KPK. The purpose of this study is to determine the role of anticorruption counselors in developing anti-corruption communities. The research method is explanatory with quantitative and qualitative approaches. The contribution of the study on the role of anticorruption counselors in developing anti-corruption communities is how big is the relevance of counseling material, the ability of anti-corruption counselors to deliver material and how capable the instructor is in motivating the spirit to be involved in preventing corruption in the Puskesmas environment until the birth of an anti-corruption movement through the anti-corruption community. Abstrak Penelitian-penelitian terdahulu membahas kasus-kasus korupsi dan upaya pemberantasan korupsi secara represif serta dampak masif dari korupsi karena semakin tingginya tindak pidana korupsi terjadi di unit-unit pelayanan publik di Indonesia. Namun, pada penelitian ini, penulis memfokuskan pada peran penyuluh antikorupsi sebagai bagian dari upaya pencegahan korupsi berupa edukasi pemberantasan korupsi di Indonesia. Upaya edukatif dilakukan sebagai bentuk dukungan kepada KPK dari serangan-serangan untuk melemahkan KPK. Tujuan penelitian ini adalah mengetahui peran penyuluh antikorupsi dalam mengembangkan komunitas antikorupsi. Metode penelitian adalah eksplanatori dengan pendekatan kuantitatif dan kualitatif. Kontribusi studi tentang peran penyuluh antikorupsi dalam mengembangkan komunitas antikorupsi adalah seberapa besar relevansi materi penyuluhan, kemampuan penyuluh antikorupsi menyampaikan materi dan seberapa mampu penyuluh dalam memotivasi semangat untuk terlibat dalam pencegahan tindak pidana korupsi di lingkungan Puskesmas sampai lahirnya sebuah gerakan antikorupsi melalui komunitas antikorupsi.